2017
DOI: 10.3390/v9100287
|View full text |Cite
|
Sign up to set email alerts
|

Sophoraflavenone G Restricts Dengue and Zika Virus Infection via RNA Polymerase Interference

Abstract: Flaviviruses including Zika, Dengue and Hepatitis C virus cause debilitating diseases in humans, and the former are emerging as global health concerns with no antiviral treatments. We investigated Sophora Flavecens, used in Chinese medicine, as a source for antiviral compounds. We isolated Sophoraflavenone G and found that it inhibited Hepatitis C replication, but not Sendai or Vesicular Stomatitis Virus. Pre- and post-infection treatments demonstrated anti-flaviviral activity against Dengue and Zika virus, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The results presented in this study underscore the entry antagonist as a promising class of antivirals and add D. apetalum to the group of medicinal plant extracts or phytochemicals that interfere with the early stage of the ZIKV replication cycle [11,12,20,41,42,43]. We recently reported that both extracts from Aphloia theiformis and Psiloxylon mauritianum , indigenous medicinal plants from Reunion Island, inactivate cell-free virions, as well as EGCG, impeding virus binding to the host cell surface by deforming ZIKV particles [12,20].…”
Section: Resultsmentioning
confidence: 83%
“…The results presented in this study underscore the entry antagonist as a promising class of antivirals and add D. apetalum to the group of medicinal plant extracts or phytochemicals that interfere with the early stage of the ZIKV replication cycle [11,12,20,41,42,43]. We recently reported that both extracts from Aphloia theiformis and Psiloxylon mauritianum , indigenous medicinal plants from Reunion Island, inactivate cell-free virions, as well as EGCG, impeding virus binding to the host cell surface by deforming ZIKV particles [12,20].…”
Section: Resultsmentioning
confidence: 83%
“…In a dose-dependent manner, the number of expressed cells significantly reduced. This finding also suggested that the polymerase of both flaviviruses was severely inhibited by SFG [104].…”
Section: Natural Inhibitors Of Arbovirusesmentioning
confidence: 67%
“…The roots of this herb have been used to treat fever, pain, and several other symptoms (He et al, 2015). Sze et al (2017) identified sophoraflavenone G derived from the roots of S. flavescens as an antiviral compound against DENV and ZIKV. The isolated molecule, sophoraflavenone G (5,7,2',4'-tetrahydroxy-8-lavandulylflavanone), is a flavanone analog of naringenin with two stereogenic centers, bearing an additional hydroxyl substituent at the 2' position and a (2R)-5-methyl-2-(prop-1en-2-yl)hex-4-en-1-yl (lavandulyl) substituent at the 8' position.…”
Section: Sophoraflavenone Gmentioning
confidence: 99%
“…To address the anti-ZIKV mechanism of the compound, the authors performed an RNA-dependent RNA-polymerase (RdRP) activity assay and observed the inhibition of this enzyme. Despite the IC 50 of 22.61 μM and the low selectivity index (SI) of sophoraflavenone G, the specific inhibition of ZIKV-RdRP has the potential to cause fewer side effects in vivo (Sze et al, 2017). However, the in vivo efficacy of sophoraflavenone G against ZIKV needs to be determined.…”
Section: Sophoraflavenone Gmentioning
confidence: 99%